2010
DOI: 10.1016/j.neuropsychologia.2010.02.005
|View full text |Cite
|
Sign up to set email alerts
|

The limits of agency in walking humans

Abstract: a b s t r a c tAn important principle of human ethics is that individuals are not responsible for actions performed when unconscious. Recent research found that the generation of an action and the building of a conscious experience of that action (agency) are distinct processes and crucial mechanisms for self-consciousness. Yet, previous agency studies have focussed on actions of a finger or hand. Here, we investigate how agents consciously monitor actions of the entire body in space during locomotion. This wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
88
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(93 citation statements)
references
References 44 publications
5
88
0
Order By: Relevance
“…One aspect of locomotion is that it is continuous and most often not immediately goal-directed (see Kannape and Blanke 2012). We have recently shown that, in a goaldirected paradigm, the limits of agency for locomotion are comparable to those of upper limb movements (Kannape et al 2010). This may reflect that at least the judgment of agency can be described by an effector-independent mechanism that predominantly depends on salient cues such as the successful completion of a given task.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One aspect of locomotion is that it is continuous and most often not immediately goal-directed (see Kannape and Blanke 2012). We have recently shown that, in a goaldirected paradigm, the limits of agency for locomotion are comparable to those of upper limb movements (Kannape et al 2010). This may reflect that at least the judgment of agency can be described by an effector-independent mechanism that predominantly depends on salient cues such as the successful completion of a given task.…”
mentioning
confidence: 99%
“…1). In each trial the participants received visual feedback of their gait for 3 s, after which they were asked to judge whether the movement that the virtual body had performed was the movement they had just made (Franck et al 2001;Kannape et al 2010). In another experimental block, counterbalanced design, participants performed the same experiment while executing the articulated serial sevens subtraction task.…”
mentioning
confidence: 99%
“…In a full body version of Nielsen's and Jeannerod's agency experiments, Kanappe and colleagues used full body tracking and avatar animation to test agency of locomotion. The results showed that we have limited conscious monitoring of our locomotive actions, indicating the limits of agency for full body motion (Kannape et al, 2010; see also Mentzer et al, 2010 for a related paradigm using auditory-motor conflicts). Once again, the relationship between technological advances in video and VR and the study of the sense of agency highlights the symbiosis between the study of the self and the emulation of self-related processes in virtual environments.…”
Section: Agencymentioning
confidence: 81%
“…In a classic experiment, Van de Bos and Jeannerod asked participants to make one of several possible hand gestures and showed them, by means of a video setup, their own hand or that of an experimenter making the same or a different gesture. Additionally, the presented hands were also rotated, such that the participants or experimenter's hand could appear to be facing down, up, left or right (van den Bos & Jeannerod, 2002; see also Kannape et al, 2010Kannape et al, , 2012. Their results indicated that when the participant and experimenter made different actions, almost no self-attribution errors occurred.…”
Section: Agencymentioning
confidence: 99%
“…By applying computational concepts developed for the visual and sensory-motor system, we proposed computational models for such self-related processing, which do not at all refer to a "self" but only to (multi)sensory signals relevant for self-related tasks. For example, vestibular signals are likely to be of importance (Schwabe and Blanke, 2008) as well as proper multi-sensory integration in sensory-motor loops (Schwabe and Blanke, 2007;Kannape et al, 2010). We have conceptualized the sense of self as a set of learning and inference algorithms for such self-related sensory signals, in particular vestibular signals, which are running on a neuronal "wetware".…”
Section: Computational Modeling Of Self-related Processingmentioning
confidence: 99%